Closing the intention-behaviour gap for sunscreen use and sun protection behaviours - Allom, Vanessa; Mullan, Barbara; Sebastian, J. (Routledge, 2013)
Objective: Two studies were conducted with the aim of closing the intention– behaviour gap for sunscreen use and sun protection behaviours by examining the influence of self-regulatory capacity on the prediction of sunscreen use (Study 1) and self-regulatory capacity and habit on sun protection behaviours (Study 2). Design: Studies were conducted online. Participants completed questionnaires and cognitive measures and then reported behaviour one week later. Main Outcome Measures: Questionnaires measuring intention and cognitive tasks measuring self-regulatory capacity were administered to 209 university students. One week later, participants reported behaviour. In Study 2, questionnaires measuring intentions, and habit and cognitive tasks measuring selfregulatory capacity were administered to 178 university students who reported behaviour one week later. Results: Intention accounted for 7.1% of variance in sunscreen use, no measures of self-regulation accounted for variance in behaviour or moderated the intention–behaviour gap (Study 1). Intention, self-regulatory capacity and habit accounted for 56.1% of variance in sun protection behaviours (Study 2). Intention, self-regulatory ability and habit predicted behaviour, while habit moderated the intention–behaviour gap. Conclusion: Interventions aimed at increasing sun protection behaviours should take into account level of intention, self-regulatory capacity and habit. Individuals may benefit from habit formation strategies and self-regulation training.